A concepção de qualidade na Revista Ensino Superior (SEMESP) no período de 2000 a 2010 - Bortolin, Letícia (Universidade Federal de São Carlos, 2017)
The present work of this objective of understanding how the conception (conceptions) of quality of the Private Higher Education expressed in the Ensino Supeiror Magazine (SEMESP) is treated, in the context of marketing, In the period from 2000 to 2010. Thus, the historical process of Expansion of Brazilian Private Higher Education was described, helping in the understanding of the quality conception of Higher Education in the Journal. In this sense, we consider that the evaluation is a means to measure if a course/institution has or not quality. In order to do so, the use of Political Epistemology (ROTHEN, 2004) was used as a methodological method for the analysis of the Journal of Higher Education, seeking to understand and understand the collective patterns (epistemology) of the Journal that guided their respective groups of editors in Propagation of their ideas, that is, their legitimation procedures. As a result, from the analyzes carried out during the period proposed by the investigation, it was understood that the magazine expresses a more focused focus on the private sector and the expansion of the same, in order to present information that helps the institutions as a means of assistance Informational. They also point out that marketing is important for the Journal, which encompasses how to propagate which courses or IES have achieved high marks/concepts in evaluations and how they did it. It was also noted that both the term evaluation and its designations as well as the term quality are not widely used, which leads us to consider that they are not matters that the Journal considers important for disclosure. It should be emphasized that, during the period investigated, there was no quality concept defined by the Journal, but it is understood that in order to have quality it is necessary to go through the evaluation processes, seeking to improve the aspects that are with unsatisfactory results, besides having good professionals And that are constantly updated. Based on the classification, it is then based on which institution has or does not have quality, and for the Journal, it is necessary to point out the aspects to be improved, as well as follow the labor market, with courses updating to meet The demands of the market. Finally, the results show that, although it is a means to find problems in the courses/institutions, the evaluation does not guarantee that these are identified as being/having quality, since the ways of evaluating the institutions/courses are equal, but Each HEI has different characteristics.
Keywords: Ensino superior privado; Qualidade; Avaliação; SEMESP; Private higher education; Quality; Evaluation; CIENCIAS HUMANAS::EDUCACAO